Learning Qawa'id Al-Lughah Al-'Arabiyyah with Active Learning Strategies / Pembelajaran Qawa’id Al-Lughah Al-‘Arabiyah dengan Strategi Pembelajaran Aktif - hafidah, hafidah (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2020)
This study aims to describe the learning of Qawa'id al Lughah al Arabiyah with an active learning strategy that makes it easy for students to learn materials that have been considered difficult. These objectives are detailed by 1) identifying active learning methods used in sharf and nahwu lectures; 3) describing the steps of learning activities for each method; 4) explaining the competency achievements obtained by students. This study used a qualitative approach with data analysis used in this study including unit processing, categorization, checking the validity of the data, and interpreting the data. The data analysis process was carried out interactively starting from data collection, data reduction, data presentation, and drawing conclusions. The results of this study explain that learning Qawa'id al-Lughah al-'Arabiyah (Sharf and Nahwu) is carried out using active learning strategies, namely Jigsaw, Small Group Discussion, Reading a load, Peer Tutors, and games. This makes students able to attain competence in three educational domains, namely attitude (affective), knowledge (cognitive), and skills (psychomotor) proportionally, and more comprehensively understand materials that have been considered difficult so far.